(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
In the production of refreshing monstrum tea, we use a number of cannabis plants, including blue and black tea plants, mint, fennel (sea fennel), spawning plants. In the preparation of blue tea, the main purpose of the evaporation process is to preserve catechins in their pure form, while in fermented black tea, the most complete oxidation of all catechins contained in the tea leaf occurs. Black tea, prepared on the basis of this technology, has a specific aroma and is well brewed.